2011
DOI: 10.1302/0301-620x.93b4.25719
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic amputations in children and adolescents

Abstract: There is no published literature detailing the demographics of paediatric amputations in the United Kingdom. We performed this review of children and adolescents referred to a regional limb-fitting centre from the 1930s to the current decade who suffered amputation as a result of trauma, and compared our data with similar cohorts from other units. Of the 93 patients included, only 11 were injured in the last 20 years. Road traffic accidents accounted for 63% of traumatic amputations. Of all amputations, 81% we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 15 publications
2
6
1
Order By: Relevance
“…Moreover, we found falls as the most common cause of amputation among the study participants (50%), followed by interpersonal violence (23.5%) and road traffic accidents (14.7%). However, this is not in line with the results of the previous studies that reported power tools (4), vehicular accidents (6), and burns (8,14) as the primary causes of trauma among children. Our findings suggest that environmental factors play a role in these incidents An essential aspect of the costs in the treatment procedure of trauma-related amputations is associated with the length of hospital stay.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…Moreover, we found falls as the most common cause of amputation among the study participants (50%), followed by interpersonal violence (23.5%) and road traffic accidents (14.7%). However, this is not in line with the results of the previous studies that reported power tools (4), vehicular accidents (6), and burns (8,14) as the primary causes of trauma among children. Our findings suggest that environmental factors play a role in these incidents An essential aspect of the costs in the treatment procedure of trauma-related amputations is associated with the length of hospital stay.…”
Section: Discussioncontrasting
confidence: 87%
“…Although there are variations based on geographical locations, most studies suggest the most frequent causes of childhood traumatic amputations as power tools, road traffic accidents, machinery, and gun-related wounds (3)(4)(5). Male children are more frequently reported as the victims, compared to their female counterparts (2,(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Patients' medical records often contain valuable information about the changes that the individual and the prosthetic service have undergone longitudinally, as evident in earlier studies. [27][28][29][30] Past studies (excluding self-reports, questionnaire-based surveys, or interviews) assessing the costs and/or repair patterns associated with UL prostheses and capturing the patient demographics have involved analyzing veteran database 10,21,22 ; insurance claims database 20 ; a retrospective analysis of the clinical records from a regional prosthetic rehabilitation center [27][28][29][30][31] ; use of secondary data from a local UL prosthetic clinic database 32 ; use of data from Workers' Compensation Board 23 ; a combination of expert consensus, survey questionnaires, and Medicare price guidelines to project future prostheses costs 24 ; and so on. There is very little literature about UL prosthetic repair rates, particularly in the United kingdom.…”
mentioning
confidence: 99%
“…Nevertheless, the rate is substantially higher in the conflict population than clinicians may be accustomed to. Similarly, 18 traumatic paediatric lower limb amputations in 2011 in Camp Bastion alone equates to a number that a major trauma centre might expect to see over four or five decades 28…”
Section: Discussionmentioning
confidence: 99%